2021
DOI: 10.15252/embr.202052325
|View full text |Cite
|
Sign up to set email alerts
|

NeutrobodyPlex—monitoring SARS‐CoV‐2 neutralizing immune responses using nanobodies

Abstract: In light of the COVID-19 pandemic, there is an ongoing need for diagnostic tools to monitor the immune status of large patient cohorts and the effectiveness of vaccination campaigns. Here, we present 11 unique nanobodies (Nbs) specific for the SARS-CoV-2 spike receptorbinding domain (RBD), of which 8 Nbs potently inhibit the interaction of RBD with angiotensin-converting enzyme 2 (ACE2) as the major viral docking site. Following detailed epitope mapping and structural analysis, we select two inhibitory Nbs, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 77 publications
(156 reference statements)
0
47
0
Order By: Relevance
“…Wagner et al [ 42 ]. have identified eleven nanobodies isolated from an immunized Alpaca with high-affinity against RBD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wagner et al [ 42 ]. have identified eleven nanobodies isolated from an immunized Alpaca with high-affinity against RBD.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether bipNb NM1267 can be a suitable nanobady for monitoring the presence and appearance of neutralizing antibodies in patients' serum, the NeutrobodyPlex method was applied. For this purpose, RBD, S1, S2, and Spike of SARSCoV-2 were incubated with NM1267 and also another well-specified nanobody as a control which targets the interface between RBD and ACE2 resulted in selection of NM1267 as a potent nanobody to detected neutralizing antibodies against RBD [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research has demonstrated that nanobodies play a significant role in several inflammatory diseases. [44][45][46] In related experiments, nanobodies specific to TLR4 treatment significantly decreased mRNA and protein levels of proinflammatory cytokines in NR8383 cells. 47 Consistently with that research, our in vitro tests showed that compared with negative nanobody treatment, specific nanobody treatment significantly suppressed mRNA and protein expression of IL1β and IL6 in HCECs stimulated by A. fumigatus.…”
Section: Effects Of Nanobodies On Proliferation Of Hcecsmentioning
confidence: 91%
“…CD4-specific Nbs were expressed and purified as previously published ( 71 , 75 ). Extracellular fragment of hCD4 comprising domains 1–4 of hCD4 and a C-terminal His6-tag was expressed in Expi293 cells according to the manufacturer’s protocol (TFS).…”
Section: Methodsmentioning
confidence: 99%
“…A peptic peptide list was generated in a preliminary LC-MS/MS experiment as described previously ( 75 ). For data-based search, no enzyme selectivity was applied; furthermore, identified peptides were manually evaluated to exclude peptides originated through cleavage after arginine, histidine, lysine, proline, and the residue after proline ( 79 ).…”
Section: Methodsmentioning
confidence: 99%